Interdisciplinary fetal-neonatal neurology training improves brain health across the lifespan - Scher, Mark S. (Frontiers in Neurology, 2024)
Integrated fetal, neonatal, and pediatric training constitute an interdisciplinary fetal-neonatal neurology (FNN) program. A dynamic neural exposome concept strengthens curriculum content. Trainees participate in mentoring committee selection for guidance during a proposed two-year program. Prenatal to postnatal clinical learning re-enforces early toxic stressor interplay that influences gene–environment interactions. Maternal-placental-fetal triad, neonatal, or childhood diseases require diagnostic and therapeutic decisions during the first 1,000 days when 80 % of neural connections contribute to life-course phenotypic expression. Pediatric follow-up through 3 years adjusts to gestational ages of preterm survivors. Cumulative reproductive, pregnancy, pediatric and adult exposome effects require educational experiences that emphasize a principle-to-practice approach to a brain capital strategy across the lifespan. More rigorous training during fetal, neonatal, and pediatric rotations will be offered to full time trainees. Adult neurology residents, medical students, and trainees from diverse disciplines will learn essential topics during time-limited rotations. Curriculum content will require periodic re-assessments using educational science standards that maintain competence while promoting creative and collaborative problem-solving. Continued career-long learning by FNN graduates will strengthen shared healthcare decisions by all stakeholders. Recognition of adaptive or maladaptive neuroplasticity mechanisms requires analytic skills that identify phenotypes associated with disease pathways. Developmental origins and life-course concepts emphasize brain health across the developmental-aging continuum, applicable to interdisciplinary research collaborations. Social determinants of health recognize diversity, equity, and inclusion priorities with each neurological intervention, particularly for those challenged with disparities. Diagnostic and therapeutic strategies must address resource challenges particularly throughout the Global South to effectively lower the worldwide burden of neurologic disease. Sustainable development goals proposed by the World Health Organization offer universally applicable guidelines in response to ongoing global and regional polycrises. Gender, race, ethnicity, and socio-economic equality promote effective preventive, rescue and reparative neuroprotective interventions. Global synergistic efforts can be enhanced by establishing leadership within academic teaching hubs in FNN training to assist with structure and guidance for smaller healthcare facilities in each community that will improve practice, education and research objectives. Reduced mortality with an improved quality of life must prioritize maternal-pediatric health and well-being to sustain brain health across each lifespan with transgenerational benefits.